A sensitive experience of the city (2012)
The article tackles the issues of perception, meaning and interpretation of the city by its own inhabitants, bringing out the importance of place, public space and urban settings in the identity and mental images of people walking and living in the city, given that everyone relates to it in its own particular way and each individual reads, interprets, comprehends and re-signifies it differently. To achieve this, the article turns up for microhistory, since it relays on the importance and validity of small events taking place in city streets to comprehend urban life in depth. It also studies the relationship between art and the city, in view of the fact that artists cast in their works their own vision of the urban, disclosing through them their individual metropolis, meaning, the one they perceive and interpret, becoming the spokesperson of the mass of anonymous inhabitants. The article concludes, amid several things, that art functions as an indicator to truly understand the city as a whole, as long as those who plan it decide to take such knowledge into account.